2020
DOI: 10.1074/jbc.ra120.013362
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrically substituted dichlorophenes inhibit N-acyl-phosphatidylethanolamine phospholipase D

Abstract: N-Acyl-phosphatidylethanolamine phospholipase D (NAPE-PLD) (EC 3.1.4.4) catalyzes the final step in the biosynthesis of N-acyl-ethanolamides. Reduced NAPE-PLD expression and activity may contribute to obesity and inflammation, but a lack of effective NAPE-PLD inhibitors has been a major obstacle to elucidating the role of NAPE-PLD and N-acyl-ethanolamide biosynthesis in these processes. The endogenous bile acid lithocholic acid (LCA) inhibits NAPE-PLD activity (with an IC50 of 68 μm), but LCA is also a highly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…The cytotoxicity of N- acylphosphatidylethanolamine-phospholipase D (NAPE-PLD) inhibition was assessed in Neuro2A cultures. Previous studies indicated that hexachlorophene and bithionol produced only small decreases in HEK293 cell viability at concentrations of 8 and 10.5 μM, respectively [ 29 ]. On the basis of this information, we tested the effect of these inhibitors on Neuro2A cells at a concentration of 10 μM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of N- acylphosphatidylethanolamine-phospholipase D (NAPE-PLD) inhibition was assessed in Neuro2A cultures. Previous studies indicated that hexachlorophene and bithionol produced only small decreases in HEK293 cell viability at concentrations of 8 and 10.5 μM, respectively [ 29 ]. On the basis of this information, we tested the effect of these inhibitors on Neuro2A cells at a concentration of 10 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of the NAPE-PLD inhibitors hexachlorophene and bithionol (Sigma-Aldrich) [ 29 ] on cell viability were tested in the presence of 2 μM FAAH inhibitor URB597. Neuro2A cells were seeded at approximately 40% confluency into a 96-well culture plate in 5% FBS/DMEM medium.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with other phospholipase classes, the known PLA1 inhibitor is not commonly reported. The main strategy of PLA1 inhibition is to design a lipid mimetic compound or phospholipid bilayer derivatives [21,22] to compete with a substrate. The idea of the auxiliary site inhibition would be of interest because the site is a solvent-accessible surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological meaning of this study remains to be assessed in vivo, these results seem promising since BA concentration spans from ~2 to 10 mM in the ileum after meal ingestion and at lower range (µM) in the blood and the liver [ 26 , 161 , 162 ]. More recently, tauroursodeoxycholic acid (TUDCA), taurohyodeoxycholic acid (THDCA) as well as α/β-MCAs and their taurine-conjugated forms have also been identified as NAPE-PLD inhibitors, although slightly less potent than LCA [ 163 ]. These studies paved the way to the design of specific NAPE-PLD modulators [ 164 ].…”
Section: Newly Identified Modulators Of Bas and Oxysterolsmentioning
confidence: 99%